Limitations and scope of the responsibility of internet service provider companies. Meta and incitement to genocide of Rohingya case - Arenal Lora, Libia (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
This paper aims to analyze the relationship between online hate speech and incitement to genocide, beside the legal responsility of companies for those crimes, based on a case study: the contribution of the company Facebook (Meta) to violence against Rohingya ethnic group in Myanmar. On the first place, a review of the events that occurred against Rohingya is carried out based on the reports prepared by the UN Independent International Investigation Mission, deployed on the ground since 2017, from which the possible existence of a genocidial intent of State was recognized. Secondly, it explores the characteristics and limitations of online speech for its calssification as a hate speech crime, not protected by freedom of expresión. Finally, it explores how these specific elements, characterizing online hate speech, opérate for the emergence and attribution of legal responsibility of the companies that provide internet services through the study of the Gambia v. Meta and Doe v. Meta before different federal courts in United States.
Keywords: online hate speech; incitement to genocide; corporate responsability